Menumbuhkan Semangat Belajar Anak dengan Penguatan dan Pengembangan Motivasi di Sanggar Pelita Medan - Muhammad Abduh Farras Gibran Nasution; Tuti Atika (Yayasan Literasi Sains Indonesia, 2022)
Learning is important for everyone in order to open their minds to be able to face various kinds of changes and challenges in the future, learning is also important for everyone, both children and adults. For children, learning may be something they think is boring, because at that age they have not found the motivation related to the importance of learning and because this lack of motivation causes their basic ability to learn to be low, they need to strengthen special motivation in order to grow their enthusiasm for learning. This is what happened to one of the children in Sanggar Pelita, the child needed to strengthen his motivation to have enthusiasm and interest in learning, the strengthening process was also carried out in the Practicum I mini project activity, using the casework intervention method by Skidmore who consists of several stages such as assessment (Assessment Phase), Program Planning, Intervention, Evaluation, and Termination. From the results of this research or practicum, it is hoped that it will have an impact in the form of increasing both interest and ability in children's learning.